TALAR NECK FRACTURE: A REVIEW OF CLINICAL PRESENTATION AND TREATMENT METHODS - Grupkovic, Jovana; Dabetic, Uros; Simić, Marko (Srpski medicinski časopis Lekarske komore, 2022)
The talus transfers the weight of the whole body onto the foot and is therefore an important factor of stability and posture. The prerequisite for successful treatment of talus neck fractures is knowledge of anatomy, understanding of the mechanisms that lead to fractures of the talus neck, knowledge of the potential complications of all treatment methods, as well as knowledge of indications for surgical treatment. About 55% of the talus surface is covered with articular cartilage, and displaced fractures lead to the destabilization of several joints. Since fractures are caused by high energy trauma, the result can easily be comminution and/or dislocation (displacement). Fractures of the talus neck can occur as an isolated injury, as well as part of polytrauma (falls from height, traffic accidents). The X-ray is the basic diagnostic tool for making an accurate diagnosis, in case of suspect talus fracture. Multi-slice computerized tomography is the most useful method for studying fracture patterns and is indispensable in planning surgical treatment. The Hawkins classification of talus neck fractures, from 1970, has remained in use to this day, while recommended treatment methods vary depending on the type of fracture. The main goal of treatment is anatomical reduction. The anatomical characteristics of the talus, the particular blood supply, as well as the "high energy" mechanism of fracture, pose a challenge for clinical evaluation and optimal treatment of talus fractures. This paper highlights the necessity of the knowledge of surgical techniques for the selection of an adequate method of treatment, in order to prevent unwanted consequences for the patient, which in the case of suboptimal treatment can be severe.
Keywords: talar neck; talar fracture; treatment